Novel Pathogenesis and Treatments for Cardiovascular Disease 2023
DOI: 10.5772/intechopen.104752
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Preeclampsia: The Role of Adiposity and Serum Adipokines

Abstract: The goal of this study was to determine serum adiponectin, leptin, resistin, visfatin, and lipids in pregnant women during the first trimester and to examine the link between these biochemical markers and preeclampsia (PE). Changes in the levels of these adipokines occur in PE, hence this study looked into the possibility of employing these biomarkers to predict the disease. This study compared first-trimester serum biochemical and anthropometric markers in pregnant women with PE to the controls. After 20 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…There are varied reports on the relationship between lipids and PE. While some researchers reported no signi cant relationship between rst trimester lipids and PE [10] others reported signi cant difference in the major lipid fractions between those with normal pregnancies and those with PE [11], [12]. Despite the fact that a strong correlation between elevated adipsin and PE has been demonstrated in a recent study which also revealed the promising value of this protein as a diagnostic tool for PE [13] to date, no relationship between adipsin and PE has been reported among pregnant women in a Ghanaian community.…”
Section: Introductionmentioning
confidence: 96%
“…There are varied reports on the relationship between lipids and PE. While some researchers reported no signi cant relationship between rst trimester lipids and PE [10] others reported signi cant difference in the major lipid fractions between those with normal pregnancies and those with PE [11], [12]. Despite the fact that a strong correlation between elevated adipsin and PE has been demonstrated in a recent study which also revealed the promising value of this protein as a diagnostic tool for PE [13] to date, no relationship between adipsin and PE has been reported among pregnant women in a Ghanaian community.…”
Section: Introductionmentioning
confidence: 96%